The sagas and conversion history: Kristni sagaand other texts - Grønlie, Siân (Universität Tübingen, 2004)
Different attitudes have been expressed about the historicity of Kristni saga since the saga was edited and translated into Latin in 1773. For historians up until the mid-twentieth century, it was a reliable source for conversion history, and its account of the missions to Iceland was used frequently in works of history in combination with Ari, the conversion þættir in Flateyjarbók, and extracts from the family sagas. More recently, however, it has been dismissed by those more sceptical about the historicity of saga literature as containing little of any value for the serious historian, and classed along with legendary and hagiographical works like Oddr and Gunnlaugr’s sagas of Óláfr Tryggvason. At the same time it is generally recognized not only that the saga’s skaldic verses are valuable historical sources, but also that some of the anecdotes not found in Ari may have a kernel of historical truth. The saga’s probable connection with the historian Sturla Þórðarson suggests that a serious historical purpose lies behind it. He collected and ordered his material on historical principles, adding both chronological and geographical details not found elsewhere, and including a passage on the missionary Þangbrandr’s stay in Borgarfjörðr. This is probably based on oral sources and its numerous place-names may reflect Sturla’s familiarity with the area. Although his written sources included hagiographical and fictional material from Oddr and Gunnlaugr’s work, Sturla is careful to revise and sometimes rewrite entirely those passages that contravene the saga’s impression of historicity. While it is difficult to tell whether he made these changes because he had access to more reliable information or purely on stylistic grounds, it is clear from comparison with other texts that the main impulse behind the saga was neither religious nor aesthetic, but historical in nature. There are several reasons why Sturla might have compiled Kristni saga or supervised its compilation. His model is usually thought to have been Snorri Sturluson’s Heimskringla and he may have wished to provide a comprehensive overview of Icelandic history just as Snorri did for the kings of Norway. In this overview, Kristni saga was the link between Landnámabók and the contemporary sagas, placing the conversion at the centre of the island’s history. Secondly, there is Sturla’s noted interest in legal matters: as in Ari’s account of the conversion, the shift from paganism to Christianity in the saga is portrayed less as a religious phenomenon than as the establishment and development of Christian law. Finally, Sturla may have seen in Iceland’s conversion an opportunity to explore the relationship between Iceland and Norway, a central problem in accounts of the conversion from Ari to the family sagas. The belief that the Norwegian king Ólafr Tryggvason brought Christianity to Iceland raised important issues concerning the political relationship between the two countries, and Iceland’s loss of independence to Norway during Sturla’s lifetime made an evaluation of that relationship especially relevant.